Antioxidant activity of red algae extract (rhodophyta) eucheuma spinosum with DPPH (2.2-diphenyl-1- picrylhydrazyl) method: Array - Nurlindah Hamrun; Nursyamsi Djamaluddin; Irvina NA. Dahri (DiscoverSys Inc., 2022)
Objective: To determine the results of the antioxidant concentration of red algae extract (Rhodophyta) Eucheuema Spinosum. Material and Methods: The type of research method used in this study is an experimental laboratory. Results: Antioxidant research results of red algae extract (Rhodophyta) Eucheuema Spinosum dry extract of ethanol fraction using DPPH (2,2-diphenyl-1- picrylhydrazyl) method had IC50 values of 702,387 µg / mL and Vitamin C IC50 of 2,588 µg / mL. Antioxidant levels of Vitamin C are more substantial. Conclusion: Antioxidants of red algae extract (Rhodophyta) Eucheuema Spinosum dry extract ethanol fraction IC50 value 702,387 µg / mL